Comparative analysis of alternative technologies of wooden building - Gayda, Serhiy; Ferents, Oleg (Forestry, Forest, Paper and Woodworking Industry, 2025)
It is substantiated that wooden construction technologies continue to develop, and wooden houses are gaining popularity due to their environmental friendliness, energy efficiency and natural appearance. This makes wood one of the most popular materials for building housing. Two main approaches to the construction of wooden houses are analyzed: traditional log houses made of rounded logs or profiled timber and modern frame technology, which allows you to create "sandwich" type houses. Each approach has its own advantages, depending on the needs of the customer, energy requirements and budget. Different types of wood cross-sections for the construction of log houses are described, in particular, profiled beams with a semicircular side and rounded logs with a compensation groove. These technologies provide high structural strength and ease of installation. It was found that the characteristics of rounding machines and stationary machines for cutting crown cups confirm the importance of precision wood processing to ensure high quality of finished structures. This affects the stability and durability of wooden buildings. It was found that traditional log houses are distinguished by natural durability and expressive aesthetics, but require significant labor and time for shrinkage. OSB systems are characterized by speed and stability of geometry, optimal for energy-efficient housebuilding, but depend on clear factory control and the quality of adhesives. It is recommended to actively introduce innovative technologies and modern equipment for the production of wooden building materials, such as rounding and stationary machines. This will increase the accuracy of manufacturing elements, reduce production costs and improve the quality of final products. It is proposed that SIP panels are best suited for quick installation and high energy efficiency, and if greater flexibility in planning and savings on logistics are required - classic frame technology with OSB sheathing.